The Concept of Appropriation in Collective Housing Design : Understanding Dwelling as a Poetic Practice - Novaković, Nevena (Writingplace, 2022)
The article aims to contribute to the theoretical debate on collective housing design by focusing on dwelling as a poetic practice. More precisely, it explores the methodological potential of the concept of appropriation that fosters the understanding of dwelling as the creative practice of human self-realization through space. It does so by interpreting selected writings of Henri Lefebvre and bringing forward exemplary housing projects. The theoretical review concludes with several principles of housing design that underline the importance of the continuity, overlapping and ‘softness’ of dwelling space. Moreover, the article conceptualizes appropriation as an analytical tool for reading the transformation of existing space made by residents. Appropriation narratives, in this way, enable housing design to understand and consider the spatial characteristics that contribute to meaningful emotional connections between space and people on different scales.